CAREER CHOICE - DECISION MAKING PROCESS (Annual of the Faculty of Philosophy in Skopje, 2013)
training and employment choice 's type. This paper represents career choice as a decision making process. Three models of decision making process in general are presented. Then, vocational decision making models are explained and their implications are discussed. The conclusion is that this approach allows to gain insight into phases, circumstances and difficulties in career decision making. The emphasize is placed on the importance of the information about oneself and occupations.
Keywords: CAREER CHOICE; DECISION MAKING PROCESS; VOCATIONAL PSYCHOLOGY